Stereotype threat theory, process, and application - Inzlicht, Michael, 1972-; Schmader, Toni, 1972- (New York ; Oxford : Oxford University Press, 2011)
Why do various racial, ethnic, religious, and gender groups differ in academic and job performance? Standard explanations for these disparities typically invoke either biological or socialization perspectives. The research summarized in this book, however, suggests that subtle reminders of cultural stereotypes play a critical yet underappreciated role in interfering with intellectual performance and in creating an illusion of group differences in ability.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Stereotypes (Social psychology); Group identity; Discrimination